Thermophysical Properties of Cryoprotective Agents IV. Thermal Capacity of Some Cryoprotective Agents, Their Aqueous Solutions and Mixtures - Todrin, A. F.; Popivnenko, L. I.; Gordienko, E. A. (Problems of Cryobiology and Cryomedicine, 2011)
The literature data for thermal capacity of water, pure cryoprotective agents, their aqueous solutions and mixtures are summarized. The empiric polynomial equations for calculation of thermal capacity of water and pure cryoprotective agents depending on temperature are derived. The empiric polynomial equations for aqueous solutions of cryoprotective agents and their mixtures depending on temperature under fixed concentrations or concentration under fixed temperatures are derived. The coefficients of polynomials for these equations are derived.